2020
DOI: 10.1111/ina.12644
|View full text |Cite
|
Sign up to set email alerts
|

Using electroencephalogram to continuously discriminate feelings of personal thermal comfort between uncomfortably hot and comfortable environments

Abstract: Thermal comfort is an important factor for the design of buildings. Although it has been well recognized that many physiological parameters are linked to the state of thermal comfort or discomfort of humans, how to use physiological signal to judge the state of thermal comfort has not been well studied. In this paper, the feasibility of continuously determining feelings of personal thermal comfort was discussed by using electroencephalogram (EEG) signals in private space. In the study, 22 subjects were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Temperature changes also affect concentration, work performance, comfort, and relaxation, and thermal effects can increase or decrease the theta power of brainwaves [17,37]. In both cases, a decrease in low-frequency energy and increase in high-frequency energy indicates a sense of comfort and relaxation [38]. These findings were replicated in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Temperature changes also affect concentration, work performance, comfort, and relaxation, and thermal effects can increase or decrease the theta power of brainwaves [17,37]. In both cases, a decrease in low-frequency energy and increase in high-frequency energy indicates a sense of comfort and relaxation [38]. These findings were replicated in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Wu et al used an eight‐channel wireless EEG recorder to record EEG signals and tried to continuously discriminate feelings of personal thermal comfort between uncomfortably hot and comfortable environments. When the temperature of the two rooms was 35℃ and 26℃, and the relative humidity is 30%–60%, the accuracy of discrimination between thermal discomfort and thermal comfort can reach almost 90% 17 . All the above studies have shown that using EEG to quantify the thermal comfort of the occupants is a promising method 18,19 …”
Section: Introductionmentioning
confidence: 98%
“…When the temperature of the two rooms was 35℃ and 26℃, and the relative humidity is 30%-60%, the accuracy of discrimination between thermal discomfort and thermal comfort can reach almost 90%. 17 All the above studies have shown that using EEG to quantify the thermal comfort of the occupants is a promising method. 18,19 Unlike thermal comfort, there are few physiological parameters that can be used to reflect cognitive performance, and EEG is the more used one.…”
mentioning
confidence: 99%
“…Accordingly, it was reported that the indoor thermal environment significantly affected the emotions, health, and productivity of tenants. Wu et al [124] investigated the possibility of continuously mediating the thermal comfort of an individual by using EEG signals in the personal space. The spectral power of the EEG signals of 22 subjects was obtained, and a discriminant model was developed using a linear discriminant analysis or an ensemble learning method with a support vector machine as a sub-classification.…”
Section: Electroencephalogrammentioning
confidence: 99%